Building Advanced Surgical Capacity at a Hospital in Port-au-Prince, Haiti. Issue 4 (June 2015) - DeGennaro, Vincent; DeGennaro, Vincent A.; Bitar, Marlon; Bitar, Jerry; Thaller, Seth
<x xml:space="preserve">Abstract</x> Abstract To improve surgical capacity in developing countries, we must take a multifaceted approach that addresses all aspects of surgery in a hospital. Foreign non-governmental organizations with expertise and resources can play a role in helping to build surgical capacity in developing countries. Episodic surgical missions can contribute to reducing the burden of the disease, but must be coupled with training of local staff to assure capacity for the future. Lack of human resources and proper infrastructure should be addressed as part of the capacity-building process. Longitudinal educational programs improve the training of local staff over time. Scaling up from episodic surgical trips to building and maintaining fully functioning surgical capacity requires sustained and repeated interventions from a large group of stakeholders. Through partnerships with local government and nongovernmental organizations, each partner can amplify the effectiveness of the other to meet the challenges of complex surgical care in low-resource settings.